2019
DOI: 10.1097/bsd.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the 100 Most Cited Articles on Intervertebral Disk Research

Abstract: Study Design: A bibliometric review of the literature. Object: To analyze and quantify the most frequently cited papers in intervertebral disk research. Summary of Background Data: The number of citations that a paper has received reflects its impact in related research area. In the field of disk research, however, it remains unknown which papers are most cited. By searching related literature databases, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The results illustrate that the USA was the leading country producing 78 of the most influential studies. This finding is in line with previously published studies in different fields [14][15][16][17][18][19]. No resource limited country was found to be involved in the top 100 studies, which showed the significant disparity of scientific research and publication trends in ApoE between low-income and developed countries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results illustrate that the USA was the leading country producing 78 of the most influential studies. This finding is in line with previously published studies in different fields [14][15][16][17][18][19]. No resource limited country was found to be involved in the top 100 studies, which showed the significant disparity of scientific research and publication trends in ApoE between low-income and developed countries.…”
Section: Discussionsupporting
confidence: 91%
“…A similar result has been reported in other studies - the most prolific period in intervertebral disk research was from 1990 to 2000 [ 16 ]. The Proceedings of the National Academy of Sciences of the United States of America was the most attractive journal for the top 100 most influential studies on ApoE.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Emerging topics Based on Figure 6 above, each circle has a different color. This shows that the keywords presented were used in research in different years(Yang et al, 2020). For…”
mentioning
confidence: 92%